Domestication of Golden Barb, Pethia gelius (Hamilton, 1822) Under Captive Condition - B.K. Mahapatra; Alkesh Pradhan; Shyam Kumar (Journal of Indian Fisheries Association, 2022)
The present practice of exporting native ornamental fish is mainly based on natural collection which is uncertain and unsustainable due to overexploitation of particular varieties of fish from natural waters. Therefore a standard captive breeding technology is required to fulfill the trade demand. Under these backgrounds, the detail study on ecological aspects and biology of indigenous Golden barb, Pethiagelius was undertaken. For domestication, fishes were collected from Dihing river of Assam, India. Eco-biological condition of the natural habitat was studied to simulate the natural condition for captive rearing. The preferred food and feeding habit of these fishes were also studied through gut content analysis. Semi-natural conditions were created in the laboratory by performing the bio-mimicry of the natural habitat. The fish were fed with Plankton, Artemia nauplii, Tubifex and chlorella twice a day. The optimum water quality was maintained throughout the period with the temperature range between 18- 28 ᵒC. By only performing the habitat simulation Pethia gelius got mature in captive condition.